Abnormal Calcium Metabolism Mediated Increased Risk of Cardiovascular Events Estimated by High Ankle-Brachial Index in Patients on Peritoneal Dialysis - Su, Xiaoyan; He, Wanbing; Zhang, Mengbi; Zhang, Yinyin; Zhu, Langjing; Chen, Jie; Huang, Hui (Frontiers in Cardiovascular Medicine, 2022)
Cardiovascular disease (CVD) is the leading cause of death in peritoneal dialysis (PD) patients. But the relationship between regular PD and the risk of major adverse cardiovascular events (MACE) remains controversial and the possible risk factors have not been not fully elucidated. This study was aimed to investigate the possible factors affecting the risk of MACE estimated by high ankle-brachial index (ABI) in PD patients. A total of 243 patients were enrolled and divided into chronic kidney diseases (CKD) stage 1, non-dialyzed CKD stage 2-5 and PD groups. The prevalence of high ABI, indicating increased MACE, was elevated with CKD progression but not further increased in PD patients. Systolic blood pressure was closely correlated with high ABI in non-dialyzed CKD patients (β = 0.059, P = 0.001). But in PD patients, abnormal serum calcium had even more crucial effect on high ABI (β = -9.853, P < 0.001). Additionally, PD patients with high ABI tended to dialyze inadequately (Kt/V < 1.7) than those with normal ABI (29.0% vs. 13.3%, P = 0.031). Further mediation analysis revealed that approximately 86.2% of the relationship between Kt/V and high ABI was mediated by serum calcium in PD patients (mediation effect = 86.2%, ab = -0.220, 95%CI: -0.381 to -0.059, P = 0.008), especially in those starting PD before 55 years old and with normal body mass index. This present study indicated that improvement of PD adequacy by maintaining calcium balance might be a promising method to reduce the risk of MACE estimated by high ABI for PD patients.